Deskilling and delanguaging African migrants in Barcelona: pathways of labour market incorporation and the value of 'global' English. (1st January 2017) - Garrido, Maria Rosa; Codó, Eva
Abstract : This article analyses the labour and social trajectories of seven multilingual and well-educated young men from Africa in the Barcelona area (Catalonia, Spain) over a 5-year period. Our data consist of life history interviews combined with ethnographic observations in a settlement non-governmental organisation (NGO). We adopt a critical sociolinguistic perspective on language and mobility which underlines the time–space dimension of migrants' emplacement and understands the value of global languages in relation to socio-economic and linguistic normativity regimes. Our findings suggest that English does not play a role in the local emplacement of these migrants, with the exceptions of the dwindling NGO sector and tourism in Barcelona. However, it indexes their transnational flows, connections and orientations. We argue that the 'ideologies of integration' of the NGOs examined background migrants' global language capitals while funnelling them into the non-qualified labour market. These agencies draw on tabula-rasa discourses that delanguage and, more generally, deskill migrants. In the current crisis, they have adopted new discourses of migration as a learning opportunity to gain experience, make contacts and learn skills. In the absence of paid work, voluntary labour is construed as intensive language practice and an opportunity to expand migrants' networks.